PENGUATAN KEPEMIMPINAN PENDIDIKAN MELALUI DIGITALISASI ARSIP DALAM MENINGKATKAN KECEPATAN DAN KETEPATAN PELAYANAN ADMINISTRASI SEKOLAH - Desvira Kumaila Z; Faiq Ulil Albab; Nabila Salsabila; Zaenu Nazmi; Siswadi (STKIP Subang, 2026)
This study aims to evaluate the role of educational leadership in supporting the process of archive digitization in order to improve the speed and accuracy of administrative services in schools. The method used is a literature review, which examines various academic sources such as journals, books, and relevant articles. Data were collected through reading, note-taking, and organizing information, and then analyzed using a qualitative descriptive approach.The findings indicate that archive digitization can enhance the efficiency of administrative services by providing easier access to information. In addition, digital systems contribute to improving data accuracy and reducing the risk of errors and data loss commonly found in manual systems. However, the successful implementation of archive digitization largely depends on educational leadership. Leaders who are responsive to technological advancements play a crucial role in guiding the use of digital systems, encouraging innovation, and fostering a positive work culture toward change. Leadership support is also essential in improving human resource readiness to effectively utilize technology. Therefore, archive digitization and educational leadership are closely interconnected in improving the quality of administrative services in schools, making them faster, more accurate, and more efficient in line with the demands of the digital era.